Dietary Carbohydrate and Protein Levels Affect the Growth Performance of Juvenile Peanut Worm (Sipunculus nudus): An LC–MS-Based Metabolomics Study - Huang, Jianqiang; Zhong, Ruzhuo; Yang, Chuangye; Wang, Qingheng; Liao, Yongshan; Deng, Yuewen (Frontiers in Marine Science, 2021)
The peanut worm (Sipunculus nudus) is an economically important fishery resource in China. To determine how dietary carbohydrate and protein levels affect the growth performance of juvenile S. nudus and identify the mechanisms underlying observed patterns, five isoenergetic and isolipidic diets with different levels of carbohydrate and protein were formulated and fed to juvenile S. nudus; the experimental groups were referred to as EG1, EG2, EG3, EG4, and EG5, respectively. After 90 days of feeding, S. nudus had significantly lower survival rates when fed D5 compared with other diets (P < 0.05), and the highest survival rate was observed in EG2 individuals. The weight gain rate and specific growth rate were significantly higher in EG2 compared with the other groups (P < 0.05). Metabolomic profiling using liquid chromatography–mass spectrometry revealed 83 significantly differential metabolites (POS: 59; NEG: 24), which were identified via an in-house MS2 database. Pathway analysis indicated that the significantly different metabolites were involved in 22 metabolic pathways (POS: 9; NEG: 13), including tyrosine, phenylalanine, and tryptophan biosynthesis; phenylalanine metabolism; D-glutamate and D-glutamine metabolism; proline and arginine metabolism; aspartate, alanine, and glutamate metabolism; and aminoacyl-tRNA biosynthesis. These analyses implied that the biosynthetic capabilities of juvenile S. nudus were greater in the EG2. The results of this research enhance our understanding of the effects of dietary carbohydrate and protein levels on the growth performance of juvenile S. nudus.